EARLY PRUNING OF EUCALYPTUS PLANTS USING GLUFOSINATE AMMONIUM - Krenchinski, Fabio Henrique [UNESP]; Costa, Renato Nunes [UNESP]; Bevilaqua, Natalia da Cunha [UNESP]; Galona, Joao Alexandre; Oliveira, Johnny Angelo de; Carbonari, Caio Antonio [UNESP]; Velini, Edivaldo Domingues [UNESP] (Univ Federal Lavras-ufla, 2018)
Eucalyptus stands out in the Brazilian silvicultural sector as the most planted tree species for commercial purposes thus, practices that facilitate management and improve wood quality are increasingly required. Although artificial mechanical pruning has been used for this crop, the use of herbicides for pruning can be more practical, rapid and have lower costs. Thus, the objective of this work was to evaluate the use of glufosinate ammonium in the chemical pruning of eucalyptus plants. Eucalyptus seedlings were transplanted into 10-L pots filled with soil and substrate and subjected to the treatments (mechanical pruning, chemical pruning, and no pruning) 90 days after transplanting. Lateral branches were cut with pruning shears for the mechanical pruning. Glufosinate ammonium (500 g a.i. ha(-1)) was applied to the sides of the plants for the chemical pruning, simulating a fieldplanting row (3.5 x 2.0 meters), using a CO2-pressurized sprayer; the untreated branches were covered with plastic bags to avoid receiving the herbicide. The percentage of artificial pruning used was 60% of the vertical height of the eucalyptus plants. Glufosinate, glutamate, and ammonia contents, electron transport rate, percentage of pruning, plant height, number of leaves, and dry matter mass of the plants were evaluated. The application of glufosinate ammonium defoliate the treated branches and did not affect significantly the parts of the plants that did not receive the herbicide regarding the evaluated compounds, and growth of the plants, denoting that glufosinate ammonium can be used for chemical pruning of eucalyptus plants.
Keywords: Ammonia; Defoliation; Chemical pruning; Herbicide; Glutamate